Ana o 3 sIgE and diagnostic algorithms reduce cost of cashew allergy diagnosis in children compared with skin prick test: A cost comparison analysis. Issue 8 (10th August 2022) - Brettig, Tim; Dalziel, Kim; Koplin, Jennifer J.; Dang, Thanh; Lange, Lars; McWilliam, Vicki; Sato, Sakura; Savvatianos, Savvas; Perrett, Kirsten P.
Abstract: Background: In the absence of a clear clinical history of reaction, diagnosis of cashew allergy using skin prick tests (SPT) or cashew‐specific IgE requires a high number of oral food challenges (OFC). By using Ana o 3 sIgE alone, or a two‐step diagnostic algorithm using cashew sIgE followed by Ana o 3 sIgE, there is a reduced need for OFC. We aimed to perform a cost comparison for both of these approaches compared with cashew SPT alone. Methods: Pooled individual‐level data from 6 studies were used to determine diagnostic accuracy and OFC rate. Two studies used cashew SPT ( n = 567, 198 allergic), with 95% positive and negative predictive values of ≥12 mm and <3 mm. Four studies were included in the pathways for Ana o 3 sIgE alone or a 2‐step algorithm incorporating cashew and Ana o 3 sIgE ( n = 271, 156 allergic). Cut‐offs used were ≥8.5kUA/L and ≤0.1kUA/L for cashew sIgE and ≥0.35kUA/L and ≤0.1kUA/L for Ana o 3 sIgE. Costs were constructed based on unit prices from hospital inpatient admissions, expenses incurred by families, individual patient data on allergic reaction types and rates, and adrenaline autoinjector carriage, applying a health system perspective. Results: Modeled data through the Ana o 3 pathway resulted in a 46.43% cost reduction (€307, 406/1000 patients) compared with using cashew SPT alone (€573, 854/1000 patients). The 2‐step algorithm resulted in a 44.94% cost reduction compared with SPT alone (€315, 952.82/1000 patients). Both the Ana o 3 pathway and 2‐step algorithm resulted in a 79%–80% reduction in OFCs compared with SPT. Conclusions: Using Ana o 3 as a standalone test for cashew allergy diagnosis or a 2‐step algorithm incorporating cashew sIgE and Ana o 3 sIgE is accurate and results in a large reduction in both OFCs and health system costs compared with cashew SPT alone.